PENGARUH VOUCHER GRATIS ONGKIR, FLASH SALE, DAN LIVE STREAMING TERHADAP IMPULSIF BUYING MAHASISWA PENGGUNA E-COMMERCE SHOPEE DI UNIVERSITAS JAMBI - Ali Syahbana Siregar; Heriberta; Helen Parkhurst (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to analyze the influence of free shipping vouchers, flash sales, and live streaming on the impulsive buying behavior of students at the University of Jambi who are active Shopee users. The research method used a quantitative approach, with 202 respondents, determined using the Slovin formula with a margin of error of 7%. The sampling technique used was purposive sampling, with the criteria being active students at the University of Jambi who use Shopee and utilize its promotional features. The research instrument was a Google Form-based questionnaire with a Likert scale of 1–5. Data analysis was conducted through validity and reliability tests, classical assumption tests, and multiple linear regression. The results showed that free shipping vouchers, flash sales, and live streaming simultaneously had a significant effect on impulsive buying. Partially, the free shipping voucher and flash sales variables had a significant positive effect, while live streaming also had a significant effect. The coefficient of determination indicates that these variables explain students' impulsive buying behavior.